High sensitivity troponin measurement in critical care: Flattering to deceive or 'never means nothing'?. (August 2020) - Hinton, Jonathan; Mariathas, Mark; Grocott, Michael PW; Curzen, Nick
Introduction: Troponin elevation is central to the diagnosis of acute type 1 myocardial infarction. It is, however, elevated in a range of other conditions, including type 2 myocardial infarction, and this setting is increasingly associated with adverse clinical outcomes. Patients within intensive care frequently have at least one organ failure together with a range of co-morbidities. Interpretation of troponin assay results in this population is challenging. This clinical uncertainty is compounded by the introduction of ever more sensitive troponin assays. Areas covered: The aims of this review are to (a) describe the currently available literature about the use of troponin assays in intensive care, (b) analyse the challenges presented by the introduction of increasingly sensitive troponin assays and (c) assess whether the role of troponin assays in intensive care may change in the future, dependent upon recent and ongoing research suggesting that they are predictive of outcome regardless of the underlying cause: the 'never means nothing' hypothesis.